SOCIOLOGY OF CULTURE - Perrin, Andrew (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course Goals 1. To survey the literature in the sociology of culture, with an emphasis on current approaches to culture 2. To stimulate ideas for empirical work in cultural sociology 3. To offer cultural tools for application to empirical research